2014
DOI: 10.1007/s11096-014-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Observational study to compare antithrombin and thrombomodulin for disseminated intravascular coagulation

Abstract: This study demonstrated no significant difference in in-hospital mortality between AT-III and rhs-TM. However, use of rhs-TM was significantly associated with decreased LOS and medical costs during hospitalization in patients with DIC associated with infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
12
1
Order By: Relevance
“…Despite the differences in DIC aetiology, the findings of our study corroborate their conclusions. However, it should be noted that the length of hospital stay in our study subjects was approximately 20 days longer than that of the subjects in Murata et al 17 . This disparity could be due to our focus on more severe patients who required mechanical ventilation for respiratory dysfunction.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Despite the differences in DIC aetiology, the findings of our study corroborate their conclusions. However, it should be noted that the length of hospital stay in our study subjects was approximately 20 days longer than that of the subjects in Murata et al 17 . This disparity could be due to our focus on more severe patients who required mechanical ventilation for respiratory dysfunction.…”
Section: Discussioncontrasting
confidence: 61%
“…A retrospective study used propensity-score matching and instrumental variable analyses to examine mechanically ventilated patients with sepsis and DIC after intestinal perforation, and found no association between TM administration and 28-day mortality 21 . Similarly, other studies using DPC databases have also reported no associations between anticoagulant therapies and mortality in septic patients with DIC 17,21 . TM administration in mechanically ventilated patients with acute respiratory distress syndrome and DIC has also been found to improve oxygenation 22 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, it was shown that factor VII deficiency is frequent in patients with infections, neoplasia, trauma, nephrotic syndrome, left heart failure, penicillin intake and clearly in patients under vitamin K dependent anticoagulation[34, 35]. However, ATIII should only be altered due to mutations[36], consumption[37] or hepatocellular dysfunction[38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…The data are coded using the International Classification of Diseases, tenth revision (ICD-10). Neonatologists routinely enter diagnoses in the patient medical records, and the use of the DPC data in clinical reports involving diverse medical specialties has been increasing [7][8][9][10][11][12], but there have been no previous studies on neonatal DIC using the DPC database in Japan. The aim of this retrospective study was to estimate the incidence and prognosis of neonatal DIC in Japan by analyzing the data available in the national administrative DPC database.…”
Section: Introductionmentioning
confidence: 99%